Manajemen Redaksional Pada Surat Kabar Harian Umum Radar Cirebon (Studi Deskriptif Kualitatif Manajemen Redaksional pada Surat Kabar Harian Umum Radar Cirebon Periode Januari-Mei 2013) - M Irfan Fazryansyah; Heriyani Agustina; Nuruzzaman Nuruzzaman (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
Mass media after the era of reform becomes the mass communication facility and instrument shaper of public opinion , it is helping in human life to exchanging ideas, sharing of experience and information in the volume of a relatively large. This research aims to understand planning, organizing, mobilizing and supervision in the management of editorial on daily newspaper of Radar Cirebon. A method of this research is descriptive qualitative, data was gathered by direct interview, observasion and availability of literature studies. Based on covered can be drawn conclusions that ( 1 ) In the planning stages, daily newspaper of Radar Cirebon well to plan, it is seen from the success of meeting and a meeting of the editor. ( 2 ) the organizing stages, the editor management has forming the organization structure and their duty to each personel.( 3 ) The mobilization phase is very important to editor management in daily newspaper of Radar Cirebon, because of mobilizarion, the management of material goes well, start from the reporting process, writing, editing till becoming the news. (4) In the phase supervision in editorial management of daily newspaper of Radar Cirebon conducted in the form of direct briefing to reporters during a news manuscript edited by the editor still experiencing a shortage of data.